2018
DOI: 10.1103/physrevx.8.041013
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative Quantum Electrodynamics in the Cherenkov Effect

Abstract: Quantum electrodynamics (QED) is one of the most precisely tested theories in the history of science, giving accurate predictions to a wide range of experimental observations. Recent experimental advances allow for the ability to probe physics on extremely short attosecond timescales, enabling ultrafast imaging of quantum dynamics. It is of great interest to extend our understanding of short-time quantum dynamics to QED, where the focus is typically on long-time observables such as S matrices, decay rates, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 80 publications
1
19
0
Order By: Relevance
“…As a key application in particle physics, Cherenkov radiation has been widely deployed for particle discrimination, i.e. the particle velocity can be determined with high accuracy by measuring the Cherenkov angle of emitted photons [4][5][6][7][8][9]. Emerging communication applications call for a route map towards the miniaturization of Cherenkov devices [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As a key application in particle physics, Cherenkov radiation has been widely deployed for particle discrimination, i.e. the particle velocity can be determined with high accuracy by measuring the Cherenkov angle of emitted photons [4][5][6][7][8][9]. Emerging communication applications call for a route map towards the miniaturization of Cherenkov devices [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding the threshold behaviors of Cherenkov radiation is of paramount importance to the development of particle physics. [ 3–10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding the threshold behaviors of Cherenkov radiation is of paramount importance to the development of particle physics. [3][4][5][6][7][8][9][10] The capability to flexibly engineer the Cherenkov threshold would benefit many practical applications including detection of cosmic rays, identification of elementary particles, novel electromagnetic sources, medical imaging and therapy, etc. [11][12][13][14][15] As a typical example, the threshold determines the sensitivity of Cherenkov detectors for particle identifications over a wide momentum range.…”
mentioning
confidence: 99%
“…These tools have enabled the study of the most fleeting and minute excitations in both light and matter. Recent works have shown that photons can shape quantum electron wavefunctions [114,116,117,[121][122][123][124][125][126][127][128][129][130][131][132][133][134][135], and that shaped electrons can in turn tailor free electron stimulated and spontaneous emission [111,[136][137][138][139][140][141][142][143][144][145][146][147].…”
mentioning
confidence: 99%